Integration of Artificial Intelligence in Islamic Religious Education Learning: Opportunities, Challenges, and Implementation Strategies Aligned with Islamic Values - Rif'ah Rif'ah; Hidayat Ma'ruf; Husnul Yaqin; Hamdan Hamdan (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the opportunities, challenges, and implementation strategies of artificial intelligence in Islamic Religious Education learning while remaining aligned with Islamic values. This research employs a library research method with a descriptive-analytical approach through the examination of various scholarly sources, including journals, books, academic articles, and educational policy documents. The data analysis technique was conducted through data reduction, categorization, interpretation, and conclusion drawing based on the relevance of the research themes. The findings indicate that the integration of AI in IRE learning offers significant opportunities to enhance learning effectiveness, personalize learning materials, improve educational accessibility, and strengthen students’ digital literacy. However, the implementation of AI also presents challenges, including the potential degradation of spiritual values, technological dependency, ethical issues in data usage, and the limited digital competence of educators. Therefore, implementation strategies are needed that emphasize the integration of Islamic values, the strengthening of teachers’ roles as moral guides, the development of curricula based on Islamic digital ethics, and educational policies that are adaptive to technological advancements